PERANAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR NEGERI DI ACEH TAMIANG - Ahmad Tarmizi; Sonny M. Ikhsan Mangkuwinata; Saiful Bahri (Hijri, 2026)
The research aims to 1) how the role of the principal as a supervisor in planning academic and managerial supervision programs to improve the quality of education 2) how far the effectiveness of the implementation of academic supervision by the principal in improving the quality of teacher learning 3) how the principal evaluates the results of academic and managerial supervision to determine follow-up in improving the quality of education 4) how the role of the principal as a supervisor in optimizing facilities, infrastructure, and funding to support the quality of education 5) what factors support and hinder the role of the principal as a supervisor in improving the quality of education. This research method uses qualitative research. The research subjects are informants consisting of principals, teachers, and school committee members. Data collection techniques include interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that learning outcomes, equity, teacher competence, learning quality, and participatory governance. This approach shows that supervision that is adaptive to local culture and school resources can produce sustainable quality improvements.